(untitled) (Global Journal of Management and Business Research, 2019)
The previous empirical findings identified knowledge identification and knowledge use as two dimensions of knowledge management; however, both areas were not extensively studied in the literature. Therefore, the paper attempted to determine the nature of knowledge identification and knowledge use on the performance of apparel sector Small and Mediumscaled Enterprises (SMEs) in Sri Lanka and also to analyze the effect of the performance of apparel SMEs. The population was determined from export performance indicators of the Export Development Board of Sri Lanka (EDB) as of 2017, and National Frame Work for SMEs in Sri Lanka was taken as the parameter to classify SMEs, which record annual turnover less than LKR 750 million. A simple random sampling technique was used as the sampling technique to ensure appropriate representation of the sample population. The owners of export-oriented apparel SMEs in Sri Lanka have been considered as respondents. A self-administrated questionnaire was used to gather primary data and SPSS 21 version was used to generate results.